Community structure of reef corals in Payar Island, Malaysia - Khodzori, Mohd Fikri Akmal; Saad, Shahbudin; Mat Zain, Khairul Amira (2016)
The community structure of reef corals were investigated by applying a method of Coral Video Transect (CVT) at seven fringing reef sites around Payar Island, Peninsular Malaysia. Field survey recorded 37 genera from 12 families, from which massive Porites and massive-platy Physogyra were found dominant in the coral assemblages. These coral genera are believe to be able to tolerate with the natural bleaching phenomenon recorded in 1998 and wide changes in environmental conditions, such as currents, wave actions and high suspended sediment concentrations. The finding of this study also showed that the reefs around Payar Island were in "poor" condition with low average coverage of live corals (14.8% ± 6.1 ). Most of the reef sites were categorized as having "poor" (8.1% - 20.8%) condition, low generic complexity (H': 1.46 - 2.17; J': 0.58 - 0.84) and low reef conservation value (CC 1). The unsustainable tourism related activities result from the increase number of tourists and shortcoming in environmental conservation are the factors which influenced poor reef condition, few generic diversity, low generic complexity and low reef conservation value in Payar Island.